Pengaruh Pengembangan Sumber Daya Manusia Terhadap Produktivitas Karyawan di Café Serlok Kopi Surabaya - Tampang, Petrus Chanel; I, Iswati; Fitriyasari, Anis (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to investigate the influence of human resource (HR) development strategies on increasing employee productivity. In the context of increasingly complex business dynamics, HR development is considered crucial for improving organizational performance. The survey method is used to collect data from respondents who are employees in various sectors. Multiple linear regression analysis is used to test the relationship between HR development strategy variables and employee productivity. The research results show that there is a positive and significant influence between HR development strategies and increasing company productivity. These findings emphasize the importance of investing in human resource development as a means of increasing employee competitiveness and performance. The practical implication of this research is that managers and organizational leaders need to pay attention to HR development strategies as an integral part of their business strategy to achieve productivity goals.